Antiviral efficacy against and replicative fitness of an XBB.1.9.1 clinical isolate - Uraki, Ryuta; Ito, Mutsumi; Kiso, Maki; Yamayoshi, Seiya; Iwatsuki-Horimoto, Kiyoko; Sakai-Tagawa, Yuko; Imai, Masaki; Koga, Michiko; Yamamoto, Shinya; Adachi, Eisuke; Saito, Makoto; Tsutsumi, Takeya; et al. (iScience, 2023)
The emergence and spread of new SARS-CoV-2 variants with mutations in the spike protein, such as the XBB.1.5 and XBB.1.9.1 sublineages, raise concerns about the efficacy of current COVID-19 vaccines and therapeutic monoclonal antibodies (mAbs). In this study, none of the mAbs we tested neutralized XBB.1.9.1 or XBB.1.5, even at the highest concentration used. We also found that the bivalent mRNA vaccine could enhance humoral immunity against XBB.1.9.1, but that XBB.1.9.1 and XBB.1.5 still evaded humoral immunity induced by vaccination or infection. Moreover, the susceptibility of XBB.1.9.1 to remdesivir, molnupiravir, nirmatrelvir, and ensitrelvir was similar to that of the ancestral strain and the XBB.1.5 isolate in vitro. Finally, we found the replicative fitness of XBB.1.9.1 to be similar to that of XBB.1.5 in hamsters. Our results suggest that XBB.1.9.1 and XBB.1.5 have similar antigenicity and replicative ability, and that the currently available COVID-19 antivirals remain effective against XBB.1.9.1. [Display omitted] •The antigenicity of XBB.1.9.1 is similar to that of XBB.1.5•XBB.1.9.1 remains susceptible to antiviral drugs•The replicative ability of XBB.1.9.1 is comparable to that of XBB.1.5 Virology; Clinical microbiology